Development of Thematic Teaching Materials Based on Local Wisdom at Madrasah Ibtidaiyah in Pagaralam City - Amir Rusdi; Amir Hamzah; Tastin Tastin; Nurlaeli Nurlaeli; Denia Widiani (AL-ISHLAH: Jurnal Pendidikan, 2023)
The objective of this research and development research is to provide educational resources centred around the Local Wisdom of Pagaralam City, specifically focusing on topic 8 "My Living Area" and sub-theme 1 "My Living Environment" for fourth-grade students at Madrasah Ibtidaiyah Pagaralam City.   The employed approach is Research and Development (RD) utilising the Tessmer development model, which has two distinct stages: the preliminary stage (including preparation and design) and the formative evaluation stage (including self-evaluation, expert review, one-to-one assessment, and small group evaluation). The participants of this developmental study consisted of fourth-grade students at A Madrasah Ibtidaiyah in Pagaralam City. The findings of this developmental research indicate that valid thematic teaching materials can be generated based on the local wisdom of Pagaralam City. The results of the walkthrough sheet at the expert review stage indicate that the material expert validator scored 78%, the design expert validator scored 64%, and the linguist validator scored 81%. These scores place the material in the valid category and confirm its suitability for use in the learning process.   The teaching materials that focus on the Local Wisdom of the City of Pagaralam can be considered practical. This is evident from the student questionnaire results, where students rated the materials as highly practical with an average percentage of 91. These materials are suitable for use in the learning process.